2014
DOI: 10.5772/57554
|View full text |Cite
|
Sign up to set email alerts
|

Human Hand Motion Analysis and Synthesis of Optimal Power Grasps for a Robotic Hand

Abstract: Biologically inspired robotic systems can find important applications in biomedical robotics, since studying and replicating human behaviour can provide new insights into motor recovery, functional substitution and human-robot interaction. The analysis of human hand motion is essential for collecting information about human hand movements useful for generalizing reaching and grasping actions on a robotic system. This paper focuses on the definition and extraction of quantitative indicators for describing optim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(31 citation statements)
references
References 35 publications
1
30
0
Order By: Relevance
“…This strategy consents to reconstruct the angle having vertex in the central marker of each finger. In [24], it is also proved that the accuracy of the motion capture data with the adopted model is in the order of 2-3 • . The adherence of the glove to the hand skin ensures that no geometric bias errors are introduced in the measurement.…”
Section: E System Evaluationmentioning
confidence: 93%
See 1 more Smart Citation
“…This strategy consents to reconstruct the angle having vertex in the central marker of each finger. In [24], it is also proved that the accuracy of the motion capture data with the adopted model is in the order of 2-3 • . The adherence of the glove to the hand skin ensures that no geometric bias errors are introduced in the measurement.…”
Section: E System Evaluationmentioning
confidence: 93%
“…Markers were placed according to the standard protocol described in [24], slightly modifying the marker position on the metacarpal bones in correspondence of the proximal acquisition point of the KPF goniometer which lies in the diaphysis of the bone. The proposed biomechanical model consists, for each finger, in a couple of segments, having the markers as extremities and placed in a 3-D space.…”
Section: E System Evaluationmentioning
confidence: 99%
“…In unstructured environ- ments, object parameters are uncertain, which makes the grasping task even more difficult and presents a big challenge for grasp stability approaches. A detailed review of all grasping techniques is out the scope of this paper and can be found in previous papers [126], [127].…”
Section: Grasp Stability and Slip Detectionmentioning
confidence: 99%
“…The high number of feasible DOFs makes the design and operation of a robotic hand very challenging. However, a careful analysis of the human fingers' motions shows that the feasible motions of phalanxes are not fully independent of one another, as outlined, for example, in [22][23][24][25]. In particular, by analysing several videos of human cylindrical grasping, one can notice that there are almost constant ratios between the motions of each phalanx during the motion of approaching an object, as also reported in [26][27][28].…”
Section: Robotic Hand Featuresmentioning
confidence: 87%